Time to onset of sustained ≥50% responder status in patients with focal (partial‐onset) seizures in three phase III studies of adjunctive brivaracetam treatment. (18th December 2016) - Klein, Pavel; Johnson, Martin E.; Schiemann, Jimmy; Whitesides, John
Summary: Time to onset of sustained ≥50% responder status (SRS) was assessed for the pooled patient population receiving brivaracetam (BRV) 50, 100, or 200 mg/day or placebo in three randomized phase III studies (NCT00464269, NCT00490035, and NCT01261325). Patients were aged ≥16 years with well‐characterized focal (partial‐onset) seizures (FS) uncontrolled by 1–2 concomitant antiepileptic drugs. After an 8‐week baseline period, patients received study drug without up‐titration for a 12‐week (84‐day) treatment period. A patient was a sustained ≥50% responder on a particular day if they completed the entire treatment period through day 84 and was a ≥50% responder (based on percent reduction in FS frequency from baseline) both on that day and every successive day until day 84 (end of treatment period). In the pooled efficacy population (N = 1, 160), 15.5%, 18.1%, and 19.4% of patients taking BRV 50, 100, or 200 mg/day, respectively, achieved SRS on day 1 versus 6.7% for placebo (p < 0.001). Statistically significant SRS was also achieved for most of the BRV‐treated groups in the three separate studies. This suggests that BRV has an early, sustained onset of action in a subset of responders. The incidence of adverse events during the first week was similar to that in the overall treatment period.